Media Credibility and COVID-19 Issues - Oktifani Winarti; Hanna Nurhaqiqi; Ratih Pandu Mustikasari (Universitas Islam Balitar, 2021)
Abstract. Today's society is believed to have a lot of access to be able to get the latest news on many things. The speed in receiving new information and awareness of existing issues is increasing. However, there are gaps in the communication process regarding the understanding of news especially in recent issues of COVID-19. This paper discusses the news-find-me perspective in understanding the social process of society to absorb and interpret COVID-19 news in Indonesia. Using a semi-structured interview and focus group discussion while highlighting Theory Reasoned Action, this rare research design and method is stressing on measuring intentions and behaviour towards informants’ perspective in potraying COVID-19. This study shows how both informants who access COVID-19 news everyday and one who is very rarely access COVID-19 news have the same doubts in media credibility on how they report the news and the data. As Previous research has found that the more a news is accessed, the higher the level of public trust in the information reported. But nowadays this has shifted to high ratings of news does not mean that the public trusts the information reported. Subsequently, the different way of behaving yet the same reason of doubts can lead to suggestions on how to make the media present news that is make people aware and take COVID-19 more seriously.